Analisis Faktor Internal dan Eksternal yang Mempengaruhi Pending Klaim BPJS Kesehatan di Rumah Sakit Patria IKKT - Ira Rizka Safia; Laela Indawati; Dina Sonia; Daniel Happy Putra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Pending claims are a chronic problem with a direct impact on the cash flow and operational efficiency of hospitals partnering with BPJS Kesehatan. Previous studies generally mapped internal and external factors separately and rarely linked them to BPJS Kesehatan's automated verification mechanisms, namely ALGORITMA and Over Utilization Review (OTOVER), leaving the proportional contribution of each mechanism unexplored. This study aims to analyze the internal and external factors influencing pending BPJS Kesehatan claims at Patria IKKT Hospital and to identify the most dominant type of pending claim. A descriptive qualitative method with a case study approach was used, involving in-depth interviews with three Casemix unit informants, observation of the claim process, and documentation study of 76 pending claim files from August to October 2025, analyzed using the Miles and Huberman interactive model. Results show that the most influential internal factor is incomplete supporting documents and medical resumes (Material) and the absence of a written SOP (Method), while external factors are dominated by coding interpretation differences between BPJS verifiers and hospital staff and rapid BPJS policy changes. The most dominant type of pending claim is ALGORITMA, accounting for 66 cases (86.8%) of 76 cases, far exceeding OTOVER (13.2%). These findings confirm that pending claims at Patria IKKT Hospital are technical-medical in nature and require strengthened clinical documentation governance and standardized SOPs